2024
DOI: 10.1039/d3fo05452g
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum 24-7 improves postoperative bloating and hard stools by modulating intestinal microbiota in patients with congenital heart disease: a randomized controlled trial

Heng Yang,
Wanqi Lan,
Chao Luo
et al.

Abstract: L. plantarum reduced symptoms of postoperative bloating and hard stools, decreased neutrophil counts, and increased lymphocyte counts in CHD patients. L. plantarum modulates the diversity and composition of the gut microbiota in CHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Probiotics, which are live microorganisms known for their health-promoting benefits, such as improving microbiome disorder, reducing gastrointestinal symptoms, inhibiting inflammation, and enhancing immunity, have garnered significant attention for addressing the abovementioned problems. 16,17 Cao et al reported that administering probiotics following gastrectomy could improve postoperative complications and facilitate the patient's early recovery through remodeling the disturbed gut microbiota. 18 Bifidobacterium , as a significant member of probiotics and a Gram-positive bacillary entity necessitating anaerobic conditions, manifests a spectrum of functionalities, including reducing inflammation, modulating immunity, protecting the intestinal mucosal barrier, maintaining intestinal microbiota homeostasis, and improving gastrointestinal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics, which are live microorganisms known for their health-promoting benefits, such as improving microbiome disorder, reducing gastrointestinal symptoms, inhibiting inflammation, and enhancing immunity, have garnered significant attention for addressing the abovementioned problems. 16,17 Cao et al reported that administering probiotics following gastrectomy could improve postoperative complications and facilitate the patient's early recovery through remodeling the disturbed gut microbiota. 18 Bifidobacterium , as a significant member of probiotics and a Gram-positive bacillary entity necessitating anaerobic conditions, manifests a spectrum of functionalities, including reducing inflammation, modulating immunity, protecting the intestinal mucosal barrier, maintaining intestinal microbiota homeostasis, and improving gastrointestinal symptoms.…”
Section: Introductionmentioning
confidence: 99%